Development of CuO doped Cts/PEG/Ag nanocomposite and their photodegradation efficiency of MB under natural Sunlight. (2017) - Geetha, D.; Ramesh, P.S.
Abstract: Copper Oxide (CuO) doped and Cts/PEG stabilized silver nanocomposites (AgNCs) were synthesized by chemical reduction method with Chitosan (Cts) and Poly ethylene glycol (PEG) as stabilizes at 80°C temperature without any toxic chemicals as reducing agents. The structural and optical characteristics were studied by various techniques. XRD pattern showed CuO doped spherical structure of Ag with grain size of 38.7 nm. Distribution of nanoparticles is confirmed by SEM and AFM. CuO doping was identified by energy dispersive spectroscopy (EDS). Dynamic Light Scattering (DLS) and Zeta potential measurements were used for average particle size/stability of AgNPs. The particle stability of the samples was reported and it changes with dopent (CuO) concentration. The CuO doped Ag was studied and it believed to originate from the interaction between Cu 2+ and Ag + ions via a super-exchange interaction. The prepared CuO doped Cts/PEG/Ag NCs exhibit enhanced photodegradation efficiency of MB than pure CuO under Sunlight.